Feeding selectivity of ichthyofauna in a tropical stream: space-time variations in trophic plasticity - Uieda, Virginia Sanches [UNESP]; Pinto, T. L. F. [UNESP] (Akademiai Kiado, 2011)
In studies on the partitioning of resources, one issue which has been largely neglected is the change in feeding habits based on the availability of food in the environment, an aspect which is dealt with here with regard to the ichthyofauna of a tropical stream. Feeding preference was analyzed for eight species of fish which consumed high percentages of aquatic insects, based on a collection of fish and invertebrates during both the dry season (June 2006) and the wet season (December 2006) and in two different stretches of the stream, one of which shaded by gallery forest (closed area) and the other just bordered by herbaceous vegetation (open area). Based on a quantitative analysis of the composition of the benthic fauna and the diet of the ichthyofauna, the electivity index was calculated in order to assess potential alterations in the feeding preferences in line with seasonal and spatial modifications to the structure of the habitat and the supply of food. The analysis of the abundance of aquatic insects in the environment showed a predominance of Ephemeroptera in all situations analyzed (areas and seasons), with this insect group being the food item preferred by the majority of fish. However, space-time variations were observed in prey selection by the ichthyofauna. The analysis of supply, consumption and preference demonstrated somewhat varied situations for the majority of species, with both high and low selectivity for items consumed in low and high percentages, with the preferred item varying both spatially and seasonally. The sole exception to this was Phalloceros harpagos, choosing Diptera-Chironomidae in all the situations analyzed.
Keywords: Benthic fauna; Electivity; Fish; Food resources; Partitioning of food